DEVELOPMENT AND EVALUATION OF A PROFESSIONAL DEVELOPMENT PROGRAM ON DESIGNING PARTICIPATORY ACTION RESEARCH PROJECTS FOR BASIC EDUCATION TEACHERS - Pineda, Hedeliza; Lorca, Anne; Cortes, Sylvester; Gador, Sunliegh; Mangompit, Rowanne Marie; Pacaldo, Frances Jay; Lorca, Elven (Advanced Education, 2022)
Anchored on Evans’ professional development (PD) model, this study aimed to develop, implement, and evaluate a professional development program on designing participatory action research (PAR) projects for basic education teachers. The teachers are from Junior and Senior High School teaching English, Mathematics, and Science. The PD program consisted of ten in-person training sessions and virtual consultations which happened in between training on AR problem conceptualization and methodology for a 14-week period. Using the mixed-methods sequential explanatory (QUAN à qual) design, the study started with a professional needs assessment participated by 18 teachers from a secondary school as a basis for the planned PD program. The teachers underwent training sessions to develop a group or participatory AR proposal as evidence of their professional growth and program outcome. At the end of the program, the English, Mathematics, and Science teachers, respectively, developed and presented their AR proposals on the (a) design and evaluation of a gamified-based instruction towards improving vocabulary skill, (b) video-based instruction in teaching basic concepts of probability, and (c) investigating the effect of contextualized learning materials in developing students’ conceptual understanding of atoms. The post-assessment results, supported by interviews, revealed that the teachers displayed behavioural, attitudinal, and intellectual developments in AR. Based on the Department of Education’s criteria for evaluating PAR proposals, all three proposals were rated acceptable for implementation by a panel of evaluators. In conclusion, the PD design and evaluation framework were important factors that enabled the participating teachers to transform their AR competencies toward developing PAR proposals for improving teaching and research in their schools.